PREVALENCE OF MALNUTRITION AMONG CHILDREN UNDER 5 YEARS IN KASSAB AND FATABRNO CAMPS AT KUTUM LOCALITY, NORTH DARFUR STATE, SUDAN - Adam Belal, Abdallah Ahmed; Fadalalla, Hamed (International Journal of Research -GRANTHAALAYAH, 2019)
Malnutrition it’s one of main problem that lead to death among children under 5 years. There is a high nutritional requirement for children under 5 years of age because they are undergoing a period of rapid growth. This descriptive cross-sectional study saw conducted in Kutum locality – North Darfur State aimed to assess the nutritional status of children under 5 years at Kassab and Fatabarno IDPs camps, in addition to assess the others factors influence child feeding practices. To achieve these aims, a survey was carried out on 101 children, age zero to 59 months in study area. Data were collected by anthropodermic measurement as well as direct interview with mothers to collect certain socio-demographic factors which were associated with the nutritional status of study population. Age was determined from mothers and weight and height were measured using standard techniques. After analyzed of obtained data by SPSS version 20 the main results are: prevalence of malnutrition in Kassab and Fatbarno IDPs camps is 15.8%, of which 6.6% is moderate acute malnutrition (MAM) and 8.9% is severe acute malnutrition (SAM), 76% of the mothers with normal children were started complementary feeding after 6 months while 69% of mothers with malnourished children were started complementary feeding before 6 months, Most of the children identified with malnourished either SAM or MAM were in the age group between 12 – 24 months representing by 63%. Then the study recommended that: raising awareness of mothers about importance of breast feeding for infant to improve nutritional status of their children, encourage complementary feeding and begin it in right age according to WHO recommendations.